The Concept of Additional State Capital to Cover the Lack of Capital in the Indonesian Investment Management Agency (LPI): Konsep Penambahan Modal Negara untuk Menutup Kekurangan Modal Lembaga Pengelola Investasi - Indrawati, Yuli (Jurnal Konstitusi, 2023)
The Investment Management Agency (LPI) is a sui generis institution managing long-term investment in Indonesia. This investment carries high business risks. UU Cipta Kerja and PP LPI regulates that should a loss that reduces the initial capital by 50%, the Government “can” increase the capital of LPI. The research problems are the concept of increasing capital to cover LPI’s initial capital shortage and its supporting mechanism to achieve state goals. This research uses a normative juridical method with a multi-disciplinary approach. The results are that the Constitutional Court as “the Guardian of the Constitution” must emphasize the concept of additional capital to cover LPI’s capital shortage must be interpreted, that the State is “obligated” to cover capital shortage as long as the existence of LPI is deemed necessary to add significant value for revenue. The approval from DPR is required to increase LPI capital, in order to achieve state goals.